An Advancements In Treatment Of Amyotrophic Lateral Sclerosis (ALS): Symptoms, causes, gene theraphy. Literature review - Ożóg, Weronika; Borowska-Łygan, Martyna; Grzech, Patrycja; Kreczyńska, Lena; Banach, Aleksandra; Zubrzycka, Weronika; Piskorowska, Klaudia; Harnicki, Patryk (Journal of Education, Health and Sport, 2025)
Introduction and Objective: Amyotrophic lateral sclerosis (ALS) is a devastating neurodegenerative disease characterized by the loss of motor neurons. Each year, amyotrophic lateral sclerosis is diagnosed in 4-5 people per 100,000 population. The disease is commonly known as Lou-Gehrig’s disease after the famous American baseball player who died two years after receiving the diagnosis at the age of 39. The etiology of the disease is not fully understood, but gene mutations that contribute to the development of ALS have been identified. Such mutations include the gene encoding superoxide dismutase type 1 (SOD1), C9orf72, TBK1 and FUS125, among others. Since the first SOD1 mutation was identified as the genetic cause of SLA, there has been a significant milestone in clinical research aimed at finding a cure for this terminal and dreaded disease. In this article, we will discuss the early symptoms of ALS, factors that increase the risk of developing the disease and, most important, the knowledge and latest treatments, such as the use of antisense oligonucleotides (ASOs). Aim of Study: This article presents up-to-date treatments for the neurodegenerative disease amyotrophic lateral sclerosis, focusing on recent clinical trials and their potential therapeutic targets. We will also review interdisciplinary treatments such as mechanical ventilation and pain management. We will also discuss factors that increase the risk of developing this incurable disease. Materials and methods: For this review article, databases such as PubMed and Google Scholar were searched. The search terms used to find relevant scientific articles included: Amyotrophic Lateral Sclerosis, ALS treatment, Tofersen, Riluzole. Ultimately, 35 research articles were cited.